Analisis Kejadian Putus Pakai Kontrasepsi di Provinsi Sumatera Utara - Putra Apriadi Siregar; Nurhayati Nurhayati; Desty Adinda; Muhammad Ancha Sitorus; Evalina Franciska Hutasoit; Robani Catursaptani (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2023)
The Family Planning Program (KB) is one of the strategies carried out by the government to suppress the increase in the rate of population growth. The Family Planning Program (KB) will not run well if there is a family planning dropout. Women of childbearing age (WUS) who experience discontinuation of family planning will increase the risk of conception. This study uses secondary data from the 2017 IDHS for 945 women of childbearing age who have used modern family planning. This study uses secondary data from the 2017 IDHS for Women of Childbearing Age (WUS). This study uses cross-tabulation to determine the distribution of husbands' approval regarding family planning devices, wanting more children, side effects of family planning, the role of family planning service providers, and the incidence of dropping out of family planning use in North Sumatra Province. The results of this study indicate that there are 238 women of childbearing age (25.8%) who drop out of family planning use and 707 women of childbearing age (74.8%). The incidence of dropping out of family planning in North Sumatra Province mostly occurs to women of childbearing age who experience side effects of family planning as many as 238 women of childbearing age and women of childbearing age who still want more children many as 67 women of childbearing age. The BKKBN of North Sumatra Province must provide training to field worker family planning on side effects of family planning to improve the skills of PLKB in providing counselling about side effects of family planning in women of childbearing age. Fieldwork family planning North Sumatra Province must provide health counselling to women of childbearing age before deciding to use contraceptive methods to minimize the side effects of family planning in women of childbearing age.